Antimicrobial, Anticancer And Antioxidant Activities Of Methanolic Extract Of Elaeis Guineensis Jacq. Leaves - Soundararajan, Vijayarathna (2012)
Malaysia, being one of the economically industrious producers of oil palm around the world correspondingly, had recognized for its assiduous and phenomenal expansion of oil palm (Elaeis guineensis) plantings. Though the plantation had considerably contributed to the nation, the by-products yielded during replanting, harvesting and pruning became controvertible. There are several by-products of oil palm, explicitly oil palm fronds (OPF) had been contributing 70% to the overall oil palm industry waste in the country which reportedly produced around 30 million tons annually of oil palm biomass, including trunks, fronds, and empty fruit bunches.